2008
DOI: 10.1007/s11427-008-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity of Clintonia udensis Trautv. et Mey. populations and its correlation with ecological factors

Abstract: The clonal diversity of Clintonia udensis Trautv. et Mey. was detected by ISSR markers among 16 populations, and its correlation with ecological factors was analyzed as well in this work. Results showed that individuals (clonal ramets) per genotype were 1.12 and 1.149 at population and species levels, respectively, and that the 16 populations were all multiclonal. The detected genotypes were localized, without exception, within populations but demonstrated relatively high clonal differentiation among populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In recent studies, the clonal diversity of C. udensis was detected using ISSR markers, and it was revealed that C. udensis occurring in China exhibited high genetic diversity at the population level and also demonstrated high genetic differentiation among populations (Wang et al . ,). Although information on phylogenetic relationships among species and the population genetic structure of a certain species has been accumulated for the genus Clintonia , little is known about the basic life‐history characteristics, including reproductive systems, of this species group.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the clonal diversity of C. udensis was detected using ISSR markers, and it was revealed that C. udensis occurring in China exhibited high genetic diversity at the population level and also demonstrated high genetic differentiation among populations (Wang et al . ,). Although information on phylogenetic relationships among species and the population genetic structure of a certain species has been accumulated for the genus Clintonia , little is known about the basic life‐history characteristics, including reproductive systems, of this species group.…”
Section: Introductionmentioning
confidence: 99%